Prevalence and seasonal dynamics of gastrointestinal nematodes of domestic fowls (Gallus gallus domesticus) in Kashmir, India - Ara, Ishrat; Khan, Humira; Syed, Tanveer; Bhat, Bilal (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: The current study was undertaken to evaluate the seasonal dependency and prevalence of gastrointestinal roundworms (nematodes) infecting domestic fowls (Gallus gallus domesticus) in Kashmir. Materials and Methods: From August 2017 through July 2019, the investigation was undertaken during each of the four seasons. We tested 400 guts obtained from varied places around the Kashmir valley for nematode infestation. The nematodes found within the digestive tract were collected and identified using a variety of identification keys under the microscope. Statistical Package for the Social Sciences was used to analyze the data (version 20). Chi-square (χ2) test was carried out to analyze the sample data. Results: 196 hosts were infected with various nematodes, indicating an overall prevalence of 49% (196/400). The findings revealed that the prevalence of Ascaridia galli was 32.97% (61/185) in the first year and 35.34% (76/215) in the second year. Heterakis gallinarum had a prevalence rate of 20.80% (38/185) in the first year and 24.18% (52/215) in the second year, whereas Capillaria spp. had a prevalence rate of 10.81% (20/185) in the first year and 12.55% (27/215) in the second year. The overall prevalence of A. galli was determined to be 34.25% in both years (August 2017–July 2019), with a mean intensity of 4.86. Summer months had the highest parasitic load. Heterakis gallinarum had a prevalence rate of 22.5% and a mean intensity of 26.83. Summer was shown to have the most considerable parasitic burden. Capillaria spp. had an overall prevalence of 11.75% and a mean intensity of 4.59; autumn had the highest parasite load. The most abundant species was identified as A. galli. It was shown that there is a significant (p < 0.01) link between seasonality and helminth parasite prevalence. Conclusion: The study’s findings indicate that these gastrointestinal nematodes are ubiquitous throughout the year, but are particularly abundant in the summer and fall seasons among domestic poultry in the study area. This study on the prevalence of gastrointestinal nematodes in Gallus gallus domesticus demonstrates the seasonality of infection rates and also offers various methods and techniques for framing effective strategies for controlling these helminthes to maximize profit from backyard chicken farming. Adv. Vet. Anim. Res., 8(2): 448-453, June 2021 http://doi.org/10.5455/javar.2021.h533